‘For Her Ladyship.’ The Enlightenment, Fasting and Dietary Practices in the Menu of an Aristocratic Lady from 1771 to 1780 - Dumanowski, Jarosław (Sensus Historiae, 2026)
The article examines food consumption, in particular fasting practices, at the court of Joanna Lubomirska, drawing on a unique collection of menus from 1771–80. The source includes menus for nearly 170 days, as well as several additional menus from 1778, allowing an analysis of recurring patterns rather than isolated examples. The author treats menus as a record of the cultural construction of meals, in which dietary norms, religious rules, and social hierarchies become visible. The discussion situates the material within the eighteenth-century context of the reception of French culinary models, the globalisation of food, and, above all, the liberalisation of Catholic fasting. The analysis shows that fasting in the duchess’s own menus is weakly marked or merely symbolic. Fasting is more clearly visible in the menus for the ‘second table’ and for the ‘young ladies,’ sometimes even in a strict form that also forbade the consumption of dairy products. In practice, parallel versions of meals appear - ‘with fasting,’ ‘with butter,’ and ‘with meat’ - which reveals both the differentiation and the negotiation of norms. The article emphasises the social dimension of fasting and its links to status, lifestyle, and the Enlightenment culture.